Comparing Monotherapy with Tadalafil or Tamsulosin and Their Combination Therapy in Men with Benign Prostatic Hyperplasia: A Randomized Clinical Trial - Karami, Hossein; Hassanzadeh-Hadad, Amin; Fallah-Karkan, Morteza (Urology Journal, 2016)
Purpose: To compare monotherapy with tadalafil or tamsulosin and their combination therapy in men with benignprostatic hyperplasia and erectile dysfunction by comparing IPSS score, prostate volume and Qmax and someother outcomes. Materials and Methods: This randomized, single-blind, paralleled group clinical trial was done in 2013 on patientswho had referred to our hospital in Tehran. All patients with lower urinary tract symptoms, benign prostatichyperplasia and any grade of erectile dysfunction were recruited. They were randomly divided into three groups(61 participants in each group): Group A received 20 mg/daily tadalafil; Group B received 0.4 mg/daily tamsulosin;Group C receieved a combination of 0.4 mg/daily tamsulosin and 20 mg/daily tadalafil. Primary outcomeswere prostate volume, prostate specific antigen, post-void residual volume, IPSS score, LUTS severity, Qmax,IIEF and erectile dysfunction severity and secondary outcome was complications. Results: The mean ± SD of ultrasonographic prostate volume was 61.4 ± 15.1 mL and prostate specific antigenlevel was 2.4 ± 1.9 ng/dl. Post-void residual level was significantly different before and after the treatment, exceptfor group A. Also, this group had no meaningful difference compared to the other groups in this regard (P > 0.05).There were significant differences between pre- and post-treatment international prostate symptom scores in eachgroup (P < 0.05). Conclusion: Combination of tamsulosin and tadalafil can improve international prostate symptom scores, internationalindex of erectile function questionnaire scores and Qmax in patients with lower urinary tract symptoms andbenign prostatic hyperplasia to more degrees than their separate use. This combination is recommended becauseof its synergistic effects, well toleration and safety.